SustainMeter: A knowledge-based system for assessing sustainability of SMEs in the fashion industry - Leo Ramos; Mike Bermeo; Andrés Quelal; Anthony Crespo; Gabriela Cajamarca; Francklin Rivas-Echeverría (SoftwareX, 2024)
This paper introduces an intelligent system to assess sustainability in small and medium-sized fashion businesses. The most relevant and common sustainability indicators were identified through literature review. Fuzzy logic was applied to handle uncertainty in evaluation. A web application was developed for use by interested companies and institutions. The usability of the system was evaluated using a questionnaire based on AttrakDiff, which showed that the system is intuitive, easy to use, novel, and attractive. The study results indicate that the system is potentially usable in evaluating and improving the sustainability of small and medium-sized enterprises in the fashion industry.